Analysis of the effect of Bacillus velezensis culture filtrate on the growth and proteome of Cladobotryum mycophilum. Issue 1 (January 2022) - Clarke, Joy; Grogan, Helen; Fitzpatrick, David; Kavanagh, Kevin
Abstract: Cladobotryum mycophilum, the causative agent of cobweb disease on Agaricus bisporus results in significant crop losses for mushroom growers worldwide. Cobweb disease is treated through strict hygiene control methods and the application of chemical fungicides but an increase in fungicide resistant Cladobotryum strains has resulted in a need to develop alternative biocontrol treatment methods. The aim of the work presented here was to evaluate the response of C. mycophilum to a Bacillus velezensis isolate to assess its potential as a novel biocontrol agent. Exposure of 48 hr C . mycophilum cultures to 25% v/v 96 hr B. velezensis culture filtrate resulted in a 57% reduction in biomass (P < 0.0002), a disruption in hyphal structure and morphology, and the appearance of aurofusarin, a secondary metabolite which is a known indicator of oxidative stress, in culture medium. Proteomic analysis of B. velezensis culture filtrate revealed the presence of peptidase 8 (subtilisin), peptide deformylase and probable cytosol aminopeptidase which are known to induce catalytic activity. Characterisation of the proteomic response of C. mycophilum following exposure to B. velezensis culture filtrate revealed an increase in the abundance of a variety of proteins associated with stress response (ISWI chromatin-remodelling complex ATPase ISW2 (+24 fold), carboxypeptidase Y precursor (+3 fold) and calmodulin (+2 fold). There was also a decrease in the abundance of proteins associated with transcription (40 S ribosomal protein S30 (−26 fold), 40 S ribosomal protein S21 (−3 fold) and carbohydrate metabolism (l -xylulose reductase (−10 fold). The results presented here indicate that B. velezensis culture filtrate is capable of inhibiting the growth of C. mycophilum and inducing a stress response, thus indicating its potential to control this important pathogen of mushrooms. Highlights: Bacillus velezensis culture filtrate inhibits growth of Cladobotryum mycophilum. Bacillus velezensis culture filtrate inhibits Cladobotryum mycophilum biomass accumulation. C. mycophilum exposed to Bacillus velezensis culture filtrate shows oxidative stress response. Bacillus velezensis culture filtrate contains range of lytic enzymes. Bacillus velezensis culture filtrate may have potential to control cobweb.